(untitled) (Boletin Médico de Postgrado, 2025)
Motivation is the fuel that mobilizes the gears of a society from the personal to the professional. There are countless factors involved in the formative and productive processes, so everything that affects the effectiveness and affectivity of the worker must be prioritized and studied. The same happens in the educational dynamics, being even more relevant because the teacher’s motivation has an impact on the formation of the new citizen who will have to face the reality of a country in constant change. The objective of this research work was to evaluate the motivational factors that influence the permanence of teachers in the Department of Preventive and Social Medicine of the Decanato de Ciencias de la Salud of the Universidad Centroccidental Lisandro Alvarado. The results show that teachers remain in the institution mainly because of intrinsic motivation, stimulated by innate job satisfaction, aware of the absence of effective extrinsic factors but committed at an individual level underpinned by high ethical, moral and citizenship principles in the formation of new generations.